2019
DOI: 10.1016/j.ijpddr.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Transient temperature fluctuations severely decrease P. falciparum susceptibility to artemisinin in vitro

Abstract: Clinical studies suggest that outcomes for hospitalised malaria patients can be improved by managed hypothermia during treatment. We examined the impact of short pulses of low temperature on ring-stage susceptibility of Plasmodium falciparum to artemisinin in vitro. The usually artemisinin-sensitive clone 3D7 exhibited substantially reduced ring-stage susceptibility to a 4-h pulse of 700 nM dihydro-artemisinin administered during a 5-h pulse of low temperature down to 17 °C. Parasite growth through the subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…In P. falciparum, ART resistance is confined to early ring stage parasites, which has been translated in laboratory conditions to increased survival in ring stage survival assays (RSAs) (6). Mutations in Pfkelch13 and PfCoronin, as well as transient (hypothermic-hyperthermic) temperatures, have been shown to enhance ring stage parasite survival in the RSAs (10,22,23). More recently, characterization of Kelch-13 interacting factors has revealed that disruption of proteins that colocalize with Kelch-13, such as the parasite endocytosis proteins ESP15, UBP-1, and others of unknown function, modulate susceptibility to ARTs (24).…”
Section: Discussionmentioning
confidence: 99%
“…In P. falciparum, ART resistance is confined to early ring stage parasites, which has been translated in laboratory conditions to increased survival in ring stage survival assays (RSAs) (6). Mutations in Pfkelch13 and PfCoronin, as well as transient (hypothermic-hyperthermic) temperatures, have been shown to enhance ring stage parasite survival in the RSAs (10,22,23). More recently, characterization of Kelch-13 interacting factors has revealed that disruption of proteins that colocalize with Kelch-13, such as the parasite endocytosis proteins ESP15, UBP-1, and others of unknown function, modulate susceptibility to ARTs (24).…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to artemisinins is unlike that of any other class of antimalarial compounds, being confined to the first few hours of intraerythrocytic development. We and others have now demonstrated this phenomenon with mutations in pfk13 (22), pfcoronin (17), pfap2, and pfubp1 as well as with transient pulses of low temperature (16), suggesting that artemisinin resistance has potentially many genetic and environmental origins. In all these cases so far, trophozoites and schizonts are fully sensitive to artemisinin.…”
Section: Figmentioning
confidence: 64%
“…We then characterized the susceptibility of these clones to artemisinin using the ring-stage survival assay (RSA) (2,16), an in vitro correlate of in vivo parasite susceptibility in which early-ring-stage parasites are exposed to a brief pulse of 700 nM DHA. Artemisinin susceptibility was also determined for three Cam3.II-derived Cambodian parasite lines (10), and the parental 3D7 line, as validated controls.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations